PENGARUH WORD OF MOUTH DAN LIFESTYLE TERHADAP KEPUTUSAN BERKUNJUNG DI JATIM PARK 3 - Novitasari, Anggun Dwi; Mulyati, Awin; Pratiwi, Ni Made Ida (Jurnal Dinamika Administrasi Bisnis, 2019)
Competition in the world of tourism business is very tight, this is known by the emergence of various new tourist attractions that provide facilities and meet the needs of visitors. Nowadays there are a lot of consumers who decide to visit tourist attractions because they follow a Lifestyle that is rife and growing. Viewed from the consumer side, communication contributes to the interest of visiting the community and as a decision maker in visiting. The marketing activity is part of the promotion of Word of mouth. This study aims to determine whether there is an influence between the variable Word of Mouth and Lifestyle on Decisions Visiting East Java Park 3. The advice that can be given to increase the visiting decision of consumers is to build a wider parking lot, give a cover on the parking lot so that visitors who come and walk from the parking lot are not exposed to heat or rain, add seats to wait for queues and add disney land rides , or adding a few tall trees and fountains in the parking area so that they are shady and cool can also be used as a place for new photos for visitors to be interested in visiting again. Keywords: Word Of Mouth, Lifestyle, and Visiting Decisions.